How does chronic endometritis influence pregnancy outcomes in endometriosis associated infertility? A retrospective cohort study - Shunhe Lin; Xi Xie; Yishan Chen; Zhenna Wang; Jinna Zhang; Chaobin Liu; Guan Lin; Yi Wang; Yuyan Guo (Reproductive Health)
Abstract Background Endometriosis (EMS) and chronic endometritis (CE) frequently coexist. This study aimed to examine the impact of CE on reproductive outcomes in patients with EMS. Methods We enrolled 685 patients with endometriosis-associated infertility from January 2018 to December 2020. The patients were divided into CE (318) and non-CE (367) groups. A subset of 123 clinically pregnant women from the CE group and 369 from the non-CE group was selected for detailed comparison. Pregnancy and delivery data were meticulously collected from hospital records and through telephone interviews. Results CE was diagnosed in 46.42% of EMS patients. Higher pregnancy rates were observed in patients with Endometriosis Fertility Index (EFI) scores of 7–10. EMS patients with CE had increased risks of placenta previa (13.01%), gestational hypertension (5.69%), and cesarean sections (59.34%). Conclusions CE, which is prevalent among EMS patients, is linked to increased risks of pregnancy complications, including placenta previa, gestational hypertension, and cesarean delivery. Although combined hysteroscopy and laparoscopy improve pregnancy rates, they demand careful management of these complications.